Doing Democracy Differently : Political Practices and Transnational Civil Society - Henrike Knappe (Budrich UniPress, 2017)
Transnational civil society networks have become increasingly important democratizing actors in global politics. Still, the exploration of democracy in such networks remains conceptually and methodologically challenging. Practice theory provides a framework to study democracy as routinized performances even in contexts of fluid boundaries, temporal relations and a diffuse constituency. The author attempts to understand how new forms of democratic practice emerge in the interaction between political actors and their structural environments.